Comparison of chitosan nanoparticles containing Lippia citriodora essential oil and citral on the induction of apoptosis in A375 melanoma cells - Abolfazl Karimivaselabadi; Mahmoud Osanloo; Ali Ghanbariasad; Elham Zarenezhad; Hossein Hosseini (BMC, 2023)
Abstract Background Using nanoparticles containing L. citriodora EO and citral has shown potential in treating skin disorders such as melanoma. Methods In this study, GC‒MS was used to analyze the chemical composition of L. citriodora essential oil (EO). The ion gelation method prepared free chitosan nanoparticles and chitosan nanoparticles containing L. citriodora EO and citral. The successful loading of the EO and citral was evaluated using ATR-FTIR. The DPPH assay measured the antioxidant effect of citral, L. citriodora EO, Citral-ChiNPs, L. citriodora-ChiNPs, and Free-ChiNPs. A375 melanoma cell viability was assessed using the MTT assay. The qPCR technique was employed to evaluate the expression of apoptotic genes, and flow cytometry was used to detect apoptosis. Results This study showed that in equal concentrations, the antioxidant properties of chitosan nanoparticles containing citral were greater than those of chitosan nanoparticles containing L. citriodora. The IC50 values of chitosan nanoparticles containing citral, L. citriodora EO, and their nonformulated states were 105.6, 199.9, 136.9, and 240 µg/ml, respectively. The gene expression results showed that the ratio of the expression of the apoptosis gene to the inhibitory gene was higher than 1 in all the samples, indicating that the conditions for apoptosis were present. Flow cytometry confirmed cell apoptosis, with 93.5 ± 0.3% in chitosan nanoparticles containing citral, 80 ± 0.2% in chitosan nanoparticles containing L. citriodora EO, 63 ± 0.3 in citral, and 42.03% in L. citriodora EO-treated cells. Conclusion The results showed that using the Nano form of L. citriodora and citral increased their efficiency in apoptosis pathways and their toxicity against 375 melanoma cancer cells.